Le catalogue des ventes de l’ONF - Gérard Marty (Revue d'anthropologie des connaissances)
The auction sales of public forests in France mainly concern standing or processed timber by lump sum. This particularity means that buyers often have to go and see the timber themselves in order to estimate the value of the lots that on the day of the sale are physically absent. This gives rise to high transaction costs and obliges the ONF (Office National des Forêts) to generate, for each individual timber lot, quantitative and qualitative data that are then inserted into a sales catalogue. This article presents the way in which this cognitive device –playing the role of a “paperback forest expert”– equips the buyers and facilitates their choice among different lots on sale. Nevertheless, as we will demonstrate, due to a difference between the ONF’s measuring convention (inspired by a volume-based approach), used to issue the catalogue, and the buyers’ one (inspired by a product-based approach), economic objectivity of the lots is a difficult aim to attain. This situation explains why the buyers keep visiting themselves the lots before the sales and why the catalogue –whose data is used to set the withdrawal price– may have a negative impact on the number of unsold lots.